Manual de patología quirúrgica pediátrica (2023)
The present manual comprehensively and exhaustively addresses surgical care for children with diverse pathologies. Special emphasis has been placed on ensuring quality and safety in care, as well as incorporating approaches aligned with the evolving needs of the Mexican context. With chapters ranging from pediatric surgical fundamentals to advanced techniques and specialized procedures, this resource becomes an indispensable ally for all those involved in the management of pediatric patients with surgical needs. The text aims to elevate the standards of pediatric surgery in our country and continue to enhance the health and quality of life of the youngest individuals.
Keywords: surgical care; mexican environment; pediatrics; child health